Incidence of deep vein thrombosis in women following caesarean section at obstetric professorial unit of De Soysa hospital for women - Sujaharan, G.; Wijeyaratne, C.N.; Randeniya, C.; Wijeyaratne, S.M.; De Silva, P. (My University, 2005)
Abstract OBJECTIVES: To determine the incidence of DVT following caesarean section, to identify the significance of various risk factors for DVT and to assess correlation of clinical features in relation to objective tests for DVT. DESIGN: A Prospective Cohort Study. SETTING: Professorial Obstetric unit, De Soysa Hospital for Women (DSHW), Colombo. METHODS: Six hundred & eleven women who underwent caesarean section during a period of nine months (1st of March 2003 to 31st of November 2003) in the above unit. Data was collected by an Interviewer-based pre-tested questionnaire, from case notes, physical examination and by doing non invasive colour Duplex ultrasonography and real time ultrasound scan. The principal investigator was trained to do real time ultrasound scan and colour Duplex at the Department of Surgery in Colombo. The principal investigator collected the data from all the subjects. The caesarean section register was maintained. Every fist two out of each set of three were recruited. Every third one was excluded. Thereafter the above mentioned information, physical exatnination and non invasive investigations (real time ultrasound scan and colour Duplex Scan) were done on 4th post operative day. MAIN OUTCOME MEASURES: Incidence of DVT, odds ratios for variables associated with DVT and the sensitivity and specificity of clinical features of DVT. RESULTS: Five hundred and four out of six hundred eleven women responded to this Study. The response-rate was 83.3 percent. Based on clinical diagnosis 14 cases were detected as having DVT. Out of these 14 cases six had confirmed DVT by objective tests. Out of the six confirmed cases one had pulmonary thromboembolism (PTE). The risk factors identified for DVT in our study include emergency caesarean section, age 35years, para 4, pre eclampsia, current major illnesses, current infections & immobility prior to surgery. The very high risk for DVT was identified as of risk score 10 or risk factors 5 or more. The sensitivity of clinical diagnosis is 42.8 percent. Thromboembolic disease is not uncommon among women after caesarean section in Sri Lanka. The long standing belief that thromboembolism is rare among Sri Lankan women is at least partly because of under diagnosis. Prompt diagnosis and treatment may prevent morbidity and mortality due to DVT and PTE.
Keywords: Deep Vein Thrombosis; Caesarean Section